2016
DOI: 10.1016/j.envint.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of modeled long-term personal exposure to ultrafine particles with inflammatory and coagulation biomarkers

Abstract: Background Long-term exposure to fine particulate matter has been linked to cardiovascular disease and systemic inflammatory responses; however, evidence is limited regarding the effects of long-term exposure to ultrafine particulate matter (UFP, <100 nm). We used a cross-sectional study design to examine the association of long-term exposure to near-highway UFP with measures of systemic inflammation and coagulation. Methods We analyzed blood samples from 408 individuals aged 40–91 years living in three near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 55 publications
(70 reference statements)
7
60
0
Order By: Relevance
“…UFP are of particular concern due to their small size, which allows them to penetrate deeper into the lungs, cross biological barriers, and be translocated to other organs where they can cause adverse health effects (Geiser et al, 2005; HEI Review Panel on Ultrafine Particulates, 2013; Oberdörster et al, 2005). Since the 2013 HEI report new studies have reported associations between traffic-generated UFP and markers of cardiovascular disease risk and mortality (Lane et al., 2016; Ostro et al, 2015; Viehmann et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UFP are of particular concern due to their small size, which allows them to penetrate deeper into the lungs, cross biological barriers, and be translocated to other organs where they can cause adverse health effects (Geiser et al, 2005; HEI Review Panel on Ultrafine Particulates, 2013; Oberdörster et al, 2005). Since the 2013 HEI report new studies have reported associations between traffic-generated UFP and markers of cardiovascular disease risk and mortality (Lane et al., 2016; Ostro et al, 2015; Viehmann et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In epidemiological studies of UFP, models based on local meteorology and traffic conditions have been developed to estimate UFP concentrations across urban areas (Aguilera et al, 2016; Lane et al, 2016). Widely-differing monitoring networks have been used to model UFP, and characterize UFP in general, including long-term stationary monitoring (Aalto et al, 2005; Cyrys et al, 2008; Moore et al, 2009), mobile monitoring (Aggarwal et al, 2012; Li et al, 2013; Padró-Martínez et al, 2012; Patton et al, 2015; Steffens et al, 2017; Weichenthal et al., 2016; Zwack et al, 2011), monitoring at central sites and multiple short-term stationary sites (Abernethy et al, 2013; Eeftens et al, 2015; Fuller et al, 2012; Hofman et al, 2016; Klompmaker et al, 2015; Meier et al, 2015; Puustinen et al, 2007; Rivera et al, 2012; Wolf et al, 2017), or a combination of mobile and stationary monitoring (Hankey and Marshall, 2015; Kerckhoffs et al., 2016; Riley et al, 2016; Sabaliauskas et al, 2015) (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…In a prior analysis of CAFEH data, we found non-significant positive associations between time-activity adjusted annual average PNC exposure (TAA-PNC) and C-reactive protein (hsCRP), interleukin-6 and tumor-necrosis factor alpha receptor II. We also found non-significant negative association with fibrinogen [24,25]. In this paper, we used the same high resolution, long-term exposure to TAA-PNC to develop explorative data on the prevalence of S/IHD (stroke, myocardial infarction, congestive heart failure, and/or angina), diabetes, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…3 UFPs have been shown to be associated with increased levels of inflammatory blood biomarkers in people living <500 m from major highways, 4,5 and UFP concentrations near highways can be twice as high as urban background concentrations. 69 …”
Section: Introductionmentioning
confidence: 99%